Reduced sulfotransferase SULT2A1 activity in patients with Alzheimer's disease - Vaňková, M; Hill, M; Velíková, M; Včelák, J; Vacínová, G; Lukášová, P; Vejražková, D; Dvořáková, K; Rusina, R; Holmerová, I; Jarolímová, E; Vaňková, H; et al. (Physiological research, 2015)
Steroids are important components in the pathophysiology of Alzheimer's disease (AD). Although their role has been studied, the corresponding metabolomic data is limited. In the present study we evaluate the role of steroid sulfotransferase SULT2A1 in the pathophysiology of AD on the basis of circulating steroids (measured by GC-MS), in which the sulfation catalyzed by SULT2A1 dominates over glucuronidation (pregnenolone/sulfate, DHEA/sulfate, androstenediol/sulfate and 5alpha-reduced pregnane and androstane catabolites). To estimate a general trend of SUL2A1 activity in AD patients we compared the ratios of steroid conjugates to their unconjugated counterparts (C/U) in controls (11 men and 22 women) and AD patients (18 men and 16 women) for individual circulating steroids after adjustment for age and BMI using ANCOVA model including the factors AD status and gender. Decreased C/U ratio for the C19 steroids demonstrate an association between attenuated sulfation of C19 steroids in adrenal zona reticularis and the pathophysiology of AD.
Keywords: Sulfotransferases; aktivace enzymů; Alzheimerova nemoc; sulfotransferasy; zona reticularis; lidé; Female; senioři; mužské pohlaví; Male; biologické markery; Aged; Zona Reticularis; Biomarkers; Alzheimer Disease; Enzyme Activation; ženské pohlaví; Humans